2021
DOI: 10.1111/1440-1681.13546
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses cholestasis‐induced liver injury and fibrosis in rats associated with the inhibition of TGFβ1–Smad3–miR21 axis and profibrogenic and hepatic injury biomarkers

Abstract: Cholestasis caused by slowing or blockage of bile flow is a serious liver disease that can lead to liver fibrosis and cirrhosis. The link between transforming growth factor beta 1 (TGFβ1), Smad family member 3 (Smad3), and microRNA 21 (miR21) in bile duct ligation (BDL)‐induced liver fibrosis in the presence and absence of the anti‐inflammatory and antioxidant compound, resveratrol (RSV), has not been previously studied. Therefore, we tested whether RSV can protect against BDL‐induced liver fibrosis associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Increasing evidence has demonstrated the potential value of miR-21 in organ injuries, i.e., cerebral injury (Yan et al, 2021), myocardial ischemia/reperfusion injury (Yuan and Fu 2021), and liver injury (ShamsEldeen et al, 2021). Besides, numerous studies have also identified the critical roles of miR-21 in cutaneous damage and wound healing (Abdel-Gawad et al, 2021;Ma et al, 2020).…”
Section: Overview Of Mir-21mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has demonstrated the potential value of miR-21 in organ injuries, i.e., cerebral injury (Yan et al, 2021), myocardial ischemia/reperfusion injury (Yuan and Fu 2021), and liver injury (ShamsEldeen et al, 2021). Besides, numerous studies have also identified the critical roles of miR-21 in cutaneous damage and wound healing (Abdel-Gawad et al, 2021;Ma et al, 2020).…”
Section: Overview Of Mir-21mentioning
confidence: 99%
“…As reported, miR-21 may regulate multiple target genes, including phosphatase and Tensin Homolog (PTEN), Transcription Factor Dp Family Member 3 (TFDP3), HMG-Box Transcription Factor 1 (HMG-Box Transcription Factor 1), Fatty Acid Binding Protein 7 (Fatty Acid Binding Protein 7), Hypoxia-inducible factor 1-alpha (HIF-α), Programmed Cell Death 4 (PDCD4), Transforming growth factor-beta (TGF-β), SMAD Family Member 7 (SMAD), Interleukin 12 (IL-12), and Tissue inhibitors of metalloproteinases 3 (TIMP-3), etc ( Zhang T et al, 2020 ). Increasing evidence has demonstrated the potential value of miR-21 in organ injuries, i.e., cerebral injury ( Yan et al, 2021 ), myocardial ischemia/reperfusion injury ( Yuan and Fu 2021 ), and liver injury ( ShamsEldeen et al, 2021 ). Besides, numerous studies have also identified the critical roles of miR-21 in cutaneous damage and wound healing ( Abdel-Gawad et al, 2021 ; Ma et al, 2020 ).…”
Section: Overview Of Mir-21mentioning
confidence: 99%
“…Previous reports documented a beneficial role of resveratrol on the liver. For example, resveratrol (i) inhibits liver steatosis [ 22 ]; (ii) inhibits the proliferation of rat HSCs [ 23 ]; (iii) inhibits liver p53 gene expression in paracetamol-mediated acute hepatic injury in rats [ 24 ]; (iv) inhibits lipopolysacharride-induced inflammation and hepatic fibrosis in mice [ 25 ]; (v) suppresses cholestasis-induced liver injury and fibrosis [ 26 ]; and (vi) reduces miR-155 induced cardiac hypertrophy [ 27 ]. Therefore, these reports urged us to speculate that the modulation of miR-155 and activation of ROS/p53-mediated hepatic fibrosis by TAA, which could be prevented by resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…13 Resveratrol (RES), which is a non-flavonoid polyphenol with a stilbene structure, is thought to have beneficial effects on the liver and to protect the liver against various injuries. [14][15][16] Previous studies have shown that RES protects against cholestasis by decreasing the accumulation of BAs and suppressing neutrophil infiltration, 17 regulating the farnesoid X receptor and BA homeostasis, 18 inhibiting profibrogenic effects, oxidative stress and inflammation, 19 and downregulating NF-κB. 20 Meanwhile, luteolin (LUT), which is a naturally occurring flavonoid, is abundantly present in a broad range of plants and has a variety of biological activities.…”
Section: Introductionmentioning
confidence: 99%